Beach family papers - Beach, Ella, -1938.; Beach, Moses Sperry, 1822-1892.; Beach, Violet
Correspondence and financial and legal papers of Moses Sperry Beach (1822-1898), newspaper publisher, and of his daughters Ella and Violet Beach. Topics include Beach's ownership of the New York Sun, Democratic politics, and his interest in and support of the graphic arts. Correspondents include Kan'ichi Asakawa, P. T. Barnum, Edward Beecher, Robert Bonner, John Ericsson, Cyrus W. Field, Edward Everett Hale, C. Grant La Farge, Charles H. Peabody, and Harriet Beecher Stowe.
Collection material in English.
Keywords: Asakawa, Kan'ichi, -- 1873-1948 -- Correspondence; Barnum, P. T. -- 1810-1891 -- Correspondence; Beecher, Edward, -- 1803-1895 -- Correspondence; Bonner, Robert, -- 1824-1899 -- Correspondence; Ericsson, John, -- 1803-1889 -- Correspondence; Field, Cyrus W. -- 1819-1892 -- Correspondence; Hale, Edward Everett, -- 1822-1909 -- Correspondence; La Farge, C. Grant -- 1862-1938 -- Correspondence; Peabody, Charles H., -- 1810-1892 -- Correspondence; Stowe, Harriet Beecher, -- 1811-1896 -- Correspondence; Democratic Party (U.S.); New York sun; American newspapers -- New York (State) -- New York; Graphic arts; Beach family